2011
DOI: 10.1080/09670262.2011.617473
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of 35 single nucleotide polymorphism markers for the brown algaFucus vesiculosus

Abstract: We characterized 35 single nucleotide polymorphism (SNP) markers for the brown alga Fucus vesiculosus. Based on existing Fucus Expressed Sequence Tag libraries for heat and desiccation-stressed tissue, SNPs were developed and confirmed by re-sequencing cDNA from a diverse panel of individuals. SNP loci were genotyped using the SEQUENOM Õ single base extension iPLEXTM system for multiplex assays on the MassARRAY Õ platform, which uses matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Our analyses revealed two clusters, coinciding with more northern and southern locations, distinguished by several analyses based on allele frequencies, and containing unique alleles within each group, in the five microsatellite loci here used. The differentiation between northern and southern lineages in F. vesiculosus was clearly established using a large number of distinct genetic markers including 13 protein coding genes [72] and 35 SNP markers [73]. The separation between these lineages of F. vesiculosus is older than the divergence between other more recently evolved species within the genus Fucus [71], highlighting their conservation value.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses revealed two clusters, coinciding with more northern and southern locations, distinguished by several analyses based on allele frequencies, and containing unique alleles within each group, in the five microsatellite loci here used. The differentiation between northern and southern lineages in F. vesiculosus was clearly established using a large number of distinct genetic markers including 13 protein coding genes [72] and 35 SNP markers [73]. The separation between these lineages of F. vesiculosus is older than the divergence between other more recently evolved species within the genus Fucus [71], highlighting their conservation value.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in assemblage composition and distribution of macroalgae have occurred in Portugal with a clear northward expansion of warm-water species (Lima et al, 2007). Range contractions of temperate macroalgal species, although not evident in Portugal (Lima et al, 2007), have occurred in areas adjacent to Portugal: the southern range edge of F. vesiculosus in Morocco (Dangeard, 1949;Benhissoune et al, 2002;Canovas et al, 2011) has recently retracted to Portugal and a decline was also recorded in the Bay of Biscay (Nicastro et al, 2013). These recent findings confirm results from previous studies, which showed a marked decline in the abundance of F. vesiculosus in northern Spain (Fernandez & Anadon, 2008;Lamela-Silvarrey et al, 2012) and suggest likely northward contraction of range edge populations in Portugal if the warming trend continues.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, genome-wide SNP genotyping has allowed for the identification of genetic signatures of adaptive genetic variation after selection by stresses in plants and insects (Namroud et al, 2008;Chávez-Galarza et al, 2013). However, to our knowledge, SNPs have been primarily used to study the overall population genetic structure in macroalgae (Canovas et al, 2011;Olsson and Korpelainen, 2013;Provan et al, 2013;Yesson et al, 2018), including the effect of water depth and light radiation on the distribution of cryptic algal species using seascape genomics (De Jode et al, 2019). Only in a few cases SNPs have been employed to detect neutral or adaptive genetic loci linking to adaptive traits, despite quantitative trait loci (QTL) identification of SNPs associated to thermal adaptation and available plasticity (Cerutti et al, 2011;Flowers et al, 2015;Avia et al, 2017).…”
Section: Populationmentioning
confidence: 99%